2012
DOI: 10.1038/ncomms2282
|View full text |Cite
|
Sign up to set email alerts
|

Delivery of chemotherapeutic drugs in tumour cell-derived microparticles

Abstract: Cellular microparticles are vesicular plasma membrane fragments with a diameter of 100-1,000 nanometres that are shed by cells in response to various physiological and artificial stimuli. Here we demonstrate that tumour cell-derived microparticles can be used as vectors to deliver chemotherapeutic drugs. We show that tumour cells incubated with chemotherapeutic drugs package these drugs into microparticles, which can be collected and used to effectively kill tumour cells in murine tumour models without typical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
371
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 399 publications
(384 citation statements)
references
References 55 publications
13
371
0
Order By: Relevance
“…Previously, we have shown that drug-packaging MPs can enter and induce tumor cell apoptosis. 15 Here, we also found that Cis-MPs were cytotoxic to H22, CT26 and Lewis lung cancer cells (Fig. 5B), which, however, was enhanced by LDI (Fig.…”
Section: Remodeling Macrophages By Combined Ldi and Cis-mps Is Explaisupporting
confidence: 68%
See 2 more Smart Citations
“…Previously, we have shown that drug-packaging MPs can enter and induce tumor cell apoptosis. 15 Here, we also found that Cis-MPs were cytotoxic to H22, CT26 and Lewis lung cancer cells (Fig. 5B), which, however, was enhanced by LDI (Fig.…”
Section: Remodeling Macrophages By Combined Ldi and Cis-mps Is Explaisupporting
confidence: 68%
“…After 18-20 h, supernatants were used for MPs isolation as described previously. 15 Briefly, supernatants were centrifuged at 1,300 rpm for 10 min to remove whole cells and then centrifuged at 5,000 rpm for 10 min and 14,000 g for 2 min to remove debris. The supernatants were further centrifuged at 14,000 g for 60 min to pellet MPs.…”
Section: Generation and Isolation Of Mpsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have highlighted that after treatment with chemotherapeutic drugs, apoptotic tumor cells can release microparticles, which may contain DAMPs that stimulate DCs and can be used to effectively kill tumor cells. 33,34 Therefore, when appropriate antigenic transfer to DCs occurs, the acute release of DAMPs may help to elicit immune responses in cancer-bearing patients. Maturation and activation of DCs is required for DC migration to T-cell regions within the lymph node.…”
Section: Discussionmentioning
confidence: 99%
“…However, the administration of Dex may induce stomach and duodenum ulceration in hepatocarcinoma patients 54 . Recently, we demonstrated that tumour cell-derived micro- * * * * particles can deliver drugs to tumour cells in vivo without side effect 55 . This new delivery technology may be helpful in overcoming the limitations of Dex in hepatocarcinoma patients.…”
Section: Discussionmentioning
confidence: 99%